Numerical Simulation Analysis of Lead Rubber Bearings (LRBs) Damage and Superstructure Response Under Near-Fault Earthquakes - Yue Ren; Ruidong Wang; Wenfu He; Wenguang Liu (Buildings)
Under the action of near fault earthquakes, the LRB bearings of long-period isolated buildings are prone to significant deformation and failure under compression shear conditions. Therefore, it is necessary to analyze the damage of LRB and its impact on the superstructure. Finite element analysis methodology was selected and Abaqus was used to simulate hysteresis curve of LRB and the separation between rubber layer and steel layer when horizontal deformation reaches 400%. A simplified four-stiffness isolation bearing model is proposed and applied to seismic isolation damage analysis on 8-story seismic structure under near-fault earthquakes. Damage on different positions and numbers of bearings are also compared. It concludes that under the compressive and shearing state, when the horizontal deformation of the isolator exceeds 300%, the stiffness enhancement section appears. Moreover, it is found that the damage of all LRBs show the most significant scale-up effect on acceleration and story drift.